Coping with organisational change in an Indonesian state-owned enterprise : the role of personality traits and emotional intelligence - Haslan, Risky Harisa (2017)
Recently, more researchers have begun to examine coping behaviour on the individual level during organisational change. This study explores the effects that emotional intelligence and personality traits might have on coping behaviour of state-owned enterprise employees during a period of organisational change. In particular, the present study (1) explores the concept of organisational change in an Indonesian state-owned enterprise, (2) creates an appropriate scale for coping with organisational change, (3) explores whether personality traits correlate with employees’ coping behaviour during organisational change, (4) explores whether emotional intelligence correlates with employees’ coping behaviour during organisational change, (5) explores whether age, gender, and tenure have moderating effects on the roles of personality traits and emotional intelligence in coping with organisational change. Conceptual frameworks were developed in line with the concepts of organisational change, coping, state-owned enterprise, personality traits, and emotional intelligence. SPSS was employed to test the proposed hypotheses. Data were collected from 300 employees of an Indonesian state-owned enterprise. The study revealed that: (1) individual coping occurred regardless of whether or not organisational change was common or was expected, (2) five main coping strategies of, resistance, problem solving, self-blame, avoidance, and obtaining information, were used to develop a Coping with Organisational Change Scale (COCS), (3) extraversion, emotional intelligence, and rank were significantly correlated with problem solving, (4) agreeableness was significantly correlated with self-blame, and (5) there were no moderating effects of age, gender, and tenure in coping with organisational change. The implications of these findings are discussed in terms of the existing literature on coping with organisational change, and the fundamental conceptual framework set out at the beginning of this research could shape the direction for future research on the construct of coping with organisational change.